A pozsonyi egyetemalapítás az oktatási helyszínek tükrében - Schmelczer-Pohánka, Éva (Per Aspera ad Astra, 2014)
There were many plans for placing the faculties and institutes of the Royal Erzsébet University (founded in 1912). Some of these would have placed the campus in the inner city area, while others intended it for the outskirts of the city. The start of the First World War had a significant effect on the operation and the development of the university venues. Finally, the University in Pozsony was able to start instruction after moving into already existing buildings. This study provides an overview of this process, the various plans and the buildings that were eventually used. (Translated by Ágnes Lengvári)